EFEKTIFITAS IMPLEMENTASI PENGEMBANGAN SDM PADA PRODUKTIVITAS KARYAWAN BAGIAN PENJUALAN - Fitriana Ayu Lestari, Ni Wayan; Suwandi, Suwandi; Turini, Turini; Dewansyah, Bilal (Jurnal EBI, 2024)
This research aims to evaluate the effectiveness of the implementation of human resource development (HR) on the productivity of sales employees at PT. Sophie Cosmetic Cirebon. HR development includes various training programs, skills improvement and competency development aimed at improving employee capabilities and performance. The research method used is qualitative with a case study approach. Data was obtained through in-depth interviews with 20 sales employees and 1 HR manager at PT. Sophie Cosmetic Cirebon. The research results show that the implementation of HR development at PT. Sophie Cosmetic Cirebon is generally effective in increasing the productivity of sales employees. Employees involved in HR development programs report significant improvements in sales skills, communication and product understanding. The implications of this research highlight the importance of planning and implementing a structured and sustainable HR development program to achieve optimal results.Keywords: Effectiveness, HR Development, Employee Productivity, Sales.